1995
DOI: 10.1203/00006450-199508000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Susceptibility to Chlordecone-Potentiated Carbon Tetrachloride Hepatotoxicity and Lethality Is Due to Hepatic Quiescence

Abstract: Previous studies revealed that postnatally developing rats are resilient to the lethal effects of chlordecone (CD) + carbon tetrachloride (CCI,) combination. The objective of this study was to investigate the underlying mechanism. We hypothesized that ongoing cell division and cell cycle progression as well as additional toxicant-induced stimulation of tissue repair help in restraining the progression of injury on the one hand, and in recovery through speedy healing on the other. Postnatally developing (20-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…These findings underscore the importance of ongoing and toxicant-stimulated cell division and tissue repair meanisms in hepatotoxidty, and the need for the inclusion of age factors in (1). Recent studies have revealed that neonates and young rats are resilient to a wide variety of structurally and mechanistically dissimilar hepatotoxicants such as CC14 (2)(3)(4)(5)(6), allyl alcohol (7), galactosamine (8), and acetaminophen (9). Furthermore, young rats are resilient to the combination of chlordecone (CD) and CC14 (4)(5)(6), which is known to cause fulminant hepatic failure (10) and 100% mortality in adult rats (10)(11)(12).…”
mentioning
confidence: 99%
“…These findings underscore the importance of ongoing and toxicant-stimulated cell division and tissue repair meanisms in hepatotoxidty, and the need for the inclusion of age factors in (1). Recent studies have revealed that neonates and young rats are resilient to a wide variety of structurally and mechanistically dissimilar hepatotoxicants such as CC14 (2)(3)(4)(5)(6), allyl alcohol (7), galactosamine (8), and acetaminophen (9). Furthermore, young rats are resilient to the combination of chlordecone (CD) and CC14 (4)(5)(6), which is known to cause fulminant hepatic failure (10) and 100% mortality in adult rats (10)(11)(12).…”
mentioning
confidence: 99%
“…The lethality study was conducted to examine if stimulated cell division is critical in the resiliency of postnatally developing rats to CD-potentiated CCl4 hepatotoxicity and lethality. This concept was tested in 45-day-old rats using CLC antimitosis because this age group is known to exhibit partial sensitivity (25% mortality) to CD + CCl4 (4,5). The administration of CLC (1 mg/kg, ip) to the ND + CCl4 group did not result in any mortality (Table 1 12 and 36 hr after the administration of CCl4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is also known that exposure to a combination of CD and CC14 results in suppression of this compensatory tissue repair in rats, allowing progression of liver injury, culminating in liver failure and animal death (10)(11)(12)17,(34)(35)(36). In contrast, young rats are resilient to CD-potentiated CC14 hepatotoxicity and lethality primarily because of ongoing liver cell division replacing dead or dying cells, thereby suppressing the progression of liver injury (4)(5)(6). Furthermore Table 2.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations